Stress analysis of transverse loading for laminated cylindrical composite pipes: An approximated 2-D elasticity solution - R. M. Guedes (2006)
The standard methodologies for plastic piping systems determine to evaluate and assess mechanical behavior of glass-fibre reinforced plastic (GRP) tubes, by applying diametrically opposed compression forces. Based on an approximate elasticity solution for cylindrical shell panel suggested by Chandrashekhara and Nanjunda Rao [Static analysis of infinite laminated cylindrical shell panel, J Aerospace Eng 11 (1998) 1-8] and multi-layered build-up procedures, a method is presented to analyse the stresses and deflections of laminated cylindrical pipes, transversely isotropic, under transverse loading conditions. The approximate solution is based on the assumption that the ratio of thickness of each ply to its middle surface radius is negligible compared to unity.